2023
DOI: 10.1111/apa.16741
|View full text |Cite
|
Sign up to set email alerts
|

Food protein‐induced enterocolitis syndrome among children in northern Sweden—A retrospective review from 2004–2018

Abstract: Aim To describe clinical presentation and development of tolerance among children with Food protein‐induced enterocolitis syndrome (FPIES) in a population in northern Sweden. Methods A retrospective review of medical records of children presenting with FPIES symptoms from 1 January 2004, to 31 May 2018. Results Sixty children (65% boys) with FPIES were included. The estimated incidence gradually increased to 0.45% in 2016–2017. The most common food triggers were cow's milk (40%), fish (37%) and oat (23%). Symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The candidates need to be the first authors of the papers, not older than 45 years of age and members of the Swedish Paediatric Society. We are delighted to announce that the prize for the best paper in 2023 will be shared by Elina Oldhoff for Human bocavirus 1 epidemiology in children in relation to virus load and codetection 2 and Magnus Öhlund for Food protein‐induced enterocolitis syndrome among children in northern Sweden—A retrospective review from 2004–2018 3 …”
Section: Swedish Paediatricians Share the Journal's Young Investigato...mentioning
confidence: 99%
“…The candidates need to be the first authors of the papers, not older than 45 years of age and members of the Swedish Paediatric Society. We are delighted to announce that the prize for the best paper in 2023 will be shared by Elina Oldhoff for Human bocavirus 1 epidemiology in children in relation to virus load and codetection 2 and Magnus Öhlund for Food protein‐induced enterocolitis syndrome among children in northern Sweden—A retrospective review from 2004–2018 3 …”
Section: Swedish Paediatricians Share the Journal's Young Investigato...mentioning
confidence: 99%
“… 7 FPIES often presents when complementary foods are introduced in a child’s diet. 9 Infantile FPIES is reported to often resolve by the time school age is reached, mainly for milk and egg. 10 Therefore, the natural history of FPIES in infants is generally favorable.…”
Section: Definition and Natural Historymentioning
confidence: 99%
“…Magnus published his paper on Food protein‐induced enterocolitis syndrome among children in northern Sweden—A retrospective review from 2004–2018 1 with Sara Liljeholm, Åsa Strinnholm and Anna Winberg. The authors described food protein‐induced enterocolitis (FPIES) and reported that the most common food triggers were cows' milk, fish and oats.…”
mentioning
confidence: 99%